A systematic review of the role of learning games in fostering mathematics education in K-12 settings. (June 2022) - Pan, Yanjun; Ke, Fengfeng; Xu, Xinhao
Abstract: In the recent decade, a number of literature reviews were conducted to examine the effectiveness of learning games. However, prior reviews typically focused on providing a synopsis of the overall research trends and the games' impact on cognitive and non-cognitive learning, without providing critical and contextual information of learning-gameplay integration or the game design features. The current review focuses on recent empirical studies that implement learning games for K-12 mathematics education during the time period of 2008–2021 via a systematic search of the databases. Forty-three papers were identified as the result of a three-stage data extraction process. We identified the trends of implementing learning games in mathematics education and the ways to designing and integrating math content in gameplay. We propose that more research is needed to examine the design and use of learning games for math learning in K-12 settings. Recommendations for future game-based learning design and research are presented. Highlights: Identifying game design elements that promote effective mathematical learning is critical. Research examining how math content is characterized in the game, and how game design affect learning, is warranted. Detailed description of the game/learning mechanics, rationales for game selection or game development should be provided. More research relevant to learning-gameplay integration should be conducted.